2015
DOI: 10.1002/anie.201411408
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Retro‐Enantio Approach To Obtain a Peptide Capable of Overcoming the Blood–Brain Barrier

Abstract: The blood-brain barrier (BBB) is a formidable physical and enzymatic barrier that tightly controls the passage of molecules from the blood to the brain. In fact, less than 2 % of all potential neurotherapeutics are able to cross it. Here, by applying the retro-enantio approach to a peptide that targets the transferrin receptor, a full protease-resistant peptide with the capacity to act as a BBB shuttle was obtained and thus enabled the transport of a variety of cargos into the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 26 publications
2
101
0
Order By: Relevance
“…During the long circulation process, the stability of targeting moiety encounters enormous challenges. It was found that peptides consisting of L-amino acids were susceptible to proteolytic degradation in plasma and the BBB enzymatic barrier, readily losing their brain targeting and tumor-homing capability [30,31]. The methods often adopted to increase peptide stability include cyclization, partial D-amino acid substitution and retro-inverso isomerization [32].…”
Section: Discussionmentioning
confidence: 99%
“…During the long circulation process, the stability of targeting moiety encounters enormous challenges. It was found that peptides consisting of L-amino acids were susceptible to proteolytic degradation in plasma and the BBB enzymatic barrier, readily losing their brain targeting and tumor-homing capability [30,31]. The methods often adopted to increase peptide stability include cyclization, partial D-amino acid substitution and retro-inverso isomerization [32].…”
Section: Discussionmentioning
confidence: 99%
“…1 Many strategies have been used to overcome this key limitation, such as intracranial injection, 2 disruption by mannitol, 3 gene therapy, 4 and endogenous transport mechanisms. 5 FUS in the presence of microbubbles remains the only non-invasive, transient, localized, and reversible way to Our group has reported the use of this technique in mice [12][13][14][21][22][23][24][25][26][27][28][29][30] and non-human primates (NHP), [31][32][33][34] but in the cases where molecules of interest were administered, they were typically co-administered with microbubbles, 13,14,28,29,35 allowing them to reach not only the brain, but also other organs through systemic circulation. Drug attachment onto the lipid shell diminishes this safety concern and introduces fewer potential sideeffects to other organs.…”
Section: Introductionmentioning
confidence: 99%
“…[47] Prades et al designed a retro-enantio 12 amino acid peptide sequence to target the TfR at a binding site different to Tf. [48] TfRs are heavily expressed in the brain microvasculature. Retro-enantio peptides share similar structure to the parent peptide but show higher stability from proteolytic cleavage.…”
Section: Targeting Ligandsmentioning
confidence: 99%
“…The retro-enantio peptide outperformed Angiopep-2, which has excellent BBB permeability, and delivered cargo, including carboxyfluorescein, iron oxide NPs and quantum dots (QDs), across the BBB. [48] In a different approach, Oller-Salvia et al synthesized a peptidomimetic motif inspired from bee venom, that was resistant to serum proteases and increased the translocation of 12 nm gold (Au) NPs by 20 times in a human cellbased BBB model. [49] Aptamers, also referred to as 'chemical Abs', [50] are short single-stranded (ss) nucleic acid sequences (ribonucleic acid (RNA) or deoxyribonucleic acid (DNA) oligonucleotides) that can be engineered to have high (e.g., nano-to picomolar) affinity to their receptors.…”
Section: Targeting Ligandsmentioning
confidence: 99%